P1-S1.44 Antimicrobial susceptibility profile of Neisseria gonorrhoeae isolates in the Province of QuÉbec - 2010. (10th July 2011) - Lefebvre, B; Bourgault, A M
Abstract : Background: Regular monitoring of antimicrobial resistance of N gonorrhoeae is necessary to detect the trend in antimicrobial resistance, increases in minimum inhibitory concentrations (MICs) and to assist in the development of treatment guidelines. Methods: In 2010, all N gonorrhoeae strains isolated in clinical laboratories throughout the province were submitted to the Laboratoire de santé publique du Québec where their susceptibility profile to azithromycin, cefixime, ceftriaxone, ciprofloxacin and spectinomycin was determined by the agar dilution method. Results: A total of 831 strains isolated from 607 males and 224 females were tested. The strains were recovered from (data available for 819 strains) the following specimens—urethra, 432; cervix, 191; anus, 100; throat, 90; eye, 4; and synovial fluid, 2. All strains were susceptible to cefixime, ceftriaxone and spectinomycin, 270 (32.5%) were resistant to ciprofloxacin and 11 (1.3%) were resistant to azithromycin (MIC ≥2 mg/l). The azithromycin resistant isolates were retrieved from 11 males aged 16–55 years (mean, 30) from the Montreal area (urethra, 8; throat, 3). The azithromycin MIC distribution was as follows—4 mg/l (n=1), 8 mg/l (n=6), 16 mg/l (n=4). No highly resistant organism (MIC>128 mg/l) was identified. Among the azithromycin resistant isolates, one was resistant to ciprofloxacin but all were susceptible to cefixime, ceftriaxone and spectinomycin. In 2010, 68 (8.2%) isolates exhibited decreased susceptibility to cefixime (MIC=0.125 mg/l [n=62] and 0.25 mg/l [n=6]). Of these 68 isolates, all were susceptible to azithromycin and ceftriaxone but all were resistant to ciprofloxacin. Only one isolate showed decreased susceptibility to ceftriaxone (MIC=0.125 mg/l)—this isolate also showed decreased susceptibility to cefixime. Conclusions: As observed elsewhere, N gonorrhoeae strains are showing a worrisome drift in susceptibility to cefixime, a first line treatment for gonococcal infections associated with resistance to ciprofloxacin. Furthermore, resistance to azithromycin, a second line treatment option, is emerging. Sustained collaborative laboratory surveillance programs are mandatory for the design of public health interventions to prevent and control gonococcal infections.